The Bimasoft Application as Computer Based Test (CBT) Learning Evaluation Media: An Analysis of the Effectiveness using Android - Mulyawansyah Mulyawansyah; Umar Umar; Ahmad Jaya (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2022)
In education, the learning process is very important because it is designed in such a way by applying various methods and learning media in order to improve the quality of education. Therefore, good and bad results can be seen in the student learning process, therefore a qualified evaluation tool is needed. This study discusses the analysis of the effectiveness of the bimasoft application as a medium for evaluating computer based test (CBT) learning using Android. The objectives of this research consist of; 1) to find out the application of the bimasoft application as a medium for evaluating computer based test (CBT) learning using android at SMAN 1 Sumbawa Besar, 2) to determine the feasibility of the bimasoft application as a medium for evaluating computer-based test (CBT) learning using android at SMAN 1 Sumbawa Besar, and 3) to determine the effectiveness of the bimasoft application as a medium for evaluating computer based test (CBT) learning using android at SMAN 1 Sumbawa Besar. The type of research used by the researcher is descriptive quantitative research. Collecting data using observation methods, questionnaires, and documentation. Furthermore, the data were analyzed using descriptive analysis techniques, validity and reliability tests. The results of the study found that the application of the bimasoft application as a medium for evaluating CBT learning using android was very good (84.64%). The feasibility of the bimasoft application as a medium for evaluating CBT learning using android with very very feasible results (92.05%) and the effectiveness of the bimasoft application as a medium of evaluating CBT learning using android with very very effective results (90.69%). So it can be concluded that the use of the bimasoft application as a medium for evaluating computer based test (CBT) learning using Android at SMAN 1 Sumbawa Besar is very effective both in terms of time effectiveness, economy, scoring, objectivity of assessment, and can reduce fraudulent actions.